Hubungan Beban Kerja dengan Kinerja Perawat di Puskesmas Cibuaya Karawang - Mulyanto, Tatag; Ismail, Didi (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Minimum service standards for Community Health Centers are guidelines that regulate the type and quality of basic services that must be provided at the district/city level. The performance achievements of the Regional Government in fulfilling the quality of service in each type of basic service in the minimum Health service standards must reach 100%. Based on data obtained from the Cibuaya Community Health Center, 5 programs were found whose target achievements were still lacking, namely health services for pregnant women 98.24%, health services for postpartum mothers 98.06%, health services for toddlers 97.47%, health services for productive age 44.63%, and health services for diabetes mellitus sufferers 84.30%. Knowing the relationship between workload and nurse performance at the Cibuaya Karawang Community Health Center. Analytical with coss sectional design. The sample in this study was all 32 nurses on duty at the Cibuaya Karawang Community Health Center. The sampling technique used total sampling. Data analysis used univariate and bivariate analysis with the chi square test. The frequency distribution of workload is mostly heavy/high (65.6%) and low performance 68.8%). There is a relationship between workload and nurse performance at the Cibuaya Karawang Community Health Center (p. value 0.023). There is a relationship between workload and nurse performance at the Cibuaya Karawang Community Health Center. It is hoped that the Community Health Center will need to evaluate and adjust employee workload so that it is not too excessive. Keywords: Workload, Performance, Nurses.  ABSTRAK Standar pelayanan minimum untuk Puskesmas merupakan pedoman yang mengatur jenis dan mutu pelayanan dasar yang harus diberikan di tingkat kabupaten/kota. Capaian kinerja Pemerintah Daerah dalam pemenuhan mutu pelayanan di setiap jenis pelayanan dasar pada Standar pelayanan minimum Kesehatan harus mencapai 100%. Berdasarkan data yang didapatkan dari Puskesmas Cibuaya ditemukan 5 program dengan capaian target yang masih kurang yaitu pelayanan kesehatan ibu hamil 98,24%, pelayanan kesehatan ibu bersalin 98,06%, pelayanan kesehatan balita 97,47%, pelayanan kesehatan usia produktif 44,63%, dan pelayanan kesehatan penderita diabetes melitus 84,30%. Mengetahui hubungan beban kerja dengan kinerja perawat di Puskesmas Cibuaya Karawang. Analitik dengan rancangan coss sectional. Sampel dalam penelitian ini adalah seluruh perawat yang bertugas di Puskesmas Cibuaya Karawang sebanyak 32 orang. Teknik pengambilan sampel menggunakan total sampling.analisa data menggunakan analisa univariat dan bivariat dengan uji chi square. Distribusi frekuensi beban kerja sebagian besar berat/tinggi (65,6%) dan kinerja kurang 68,8%). Ada hubungan beban kerja dengan kinerja perawat di Puskesmas Cibuaya Karawang (p. value 0,023). Ada hubungan beban kerja dengan kinerja perawat di Puskesmas Cibuaya Karawang. Diharapkan Puskesmas perlu melakukan evaluasi dan penyesuaian beban kerja pegawai agar tidak terlalu berlebihan Kata Kunci: Beban Kerja, Kinerja, Perawat.